2016
DOI: 10.3109/02699206.2016.1147082
|View full text |Cite
|
Sign up to set email alerts
|

Volubility of the human infant: Effects of parental interaction (or lack of it)

Abstract: Although parental volubility, or amount of talk, has received considerable recent attention, infant volubility has received comparatively little attention despite its potential significance for communicative risk status and later linguistic and cognitive outcomes. Volubility of 16 typically developing infants from 2 to 11 months of age was longitudinally investigated in the present study across three social circumstances: parent talking to infant, parent not talking to infant and parent talking to interviewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
2
33
0
2
Order By: Relevance
“…Infants in their home setting may be more likely to vocalize than infants in less familiar contexts. Previous evidence also suggests that the presence of a stranger may reduce volubility in infants [Iyer, Denson, Lazar, & Oller, 2016]. It is also possible that the age difference between these samples contributed to this discrepancy.…”
Section: Discussionmentioning
confidence: 87%
“…Infants in their home setting may be more likely to vocalize than infants in less familiar contexts. Previous evidence also suggests that the presence of a stranger may reduce volubility in infants [Iyer, Denson, Lazar, & Oller, 2016]. It is also possible that the age difference between these samples contributed to this discrepancy.…”
Section: Discussionmentioning
confidence: 87%
“…Also in a small-scale study with just 16 minutes of recording per infant at 6-8 months, 80 infants produced more vocalizations when playing alone with toys than when engaged socially 81 (35). Another recent observational study found no significant difference in protophone volubility 82 between a recording circumstance where parents talked to infants compared to circumstances where parents were in the same room and silent or not present in the room at all, suggesting that 84 infants had an "independent inclination to vocalize spontaneously" (p. 481) (36) in the absence 85 of social interaction. Importantly, the rate of protophone production has been reported to be very 86 high, >4 protophones per minute during all-day audio recordings, across the entire first year, and 87 even when infants were judged to be alone in a room, the rate was >3 per minute (37).…”
Section: Development 68mentioning
confidence: 97%
“…When evaluating the emergence of canonical babbling, there is reason to consider potential differences in social and endogenous motivations behind the production of these advanced vocal forms. Considerable research has evaluated the role of social interaction in infant vocal development and the emergence of language (Franklin et al, 2013;Gros-Louis et al, 2014;Hsu & Fogel, 2001;Iyer et al, 2016;Lee et al, 2018). Caregivers are known to elicit and maintain "protoconversations" (Bateson, 1975), supporting the emergence of mature vocal stages such as canonical syllables and words (Bråten, 1988;Golinkoff et al, 1992;Rochat et al, 1999).…”
Section: The Social and Endogenous Nature Of Infant Vocalizationsmentioning
confidence: 99%